The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1016/j.jsps.2015.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes and practices of the general public toward sun exposure and protection: A national survey in Saudi Arabia

Abstract: Many international studies have been conducted to assess the knowledge, attitudes and practices (KAP) of the public toward sun exposure and sun-protection measures. However, there are scarce data on these factors from the Middle East. This study aimed to explore the KAP of the public toward sun exposure and sun-protection measures among Saudis. A cross-sectional survey using a specially designed questionnaire was conducted on a stratified random sample of the general population in the five geographical regions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
72
3
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(95 citation statements)
references
References 24 publications
(26 reference statements)
10
72
3
7
Order By: Relevance
“…In a cross-sectional study of the general population in Qassim, only 8.3% were found to use sunscreen [6]. Another cross-sectional study done in different regions of Saudi Arabia showed that approximately 24% of the general population use sunscreen [7]. Use of sunscreen among students in a Saudi university was approximately 35% [8].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In a cross-sectional study of the general population in Qassim, only 8.3% were found to use sunscreen [6]. Another cross-sectional study done in different regions of Saudi Arabia showed that approximately 24% of the general population use sunscreen [7]. Use of sunscreen among students in a Saudi university was approximately 35% [8].…”
Section: Discussionmentioning
confidence: 99%
“…Factors associated with sunscreen use in our study were female gender, high family income, sunburn history, tanning bed use, and use of other sun protection methods. Sunscreen was used more in females and people of higher social class in previous local studies [6][7][8].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The mechanism of sunscreens have two different modes which is by absorbing or reflecting 1 ultraviolet radiations . Light is the major environmental component to which skin is exposed daily and the white light comprises of UV radiations.…”
Section: Introductionmentioning
confidence: 99%